2016
DOI: 10.4103/0971-9261.176969
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatoblastoma masquerading as hepatoblastoma: A diagnostic dilemma

Abstract: Clinicoradiological and histopathological differentiation of pancreatoblastoma from hepatoblastoma can often be a challenge in clinical practice owing to their peculiar resemblance. We report a case of a 4-year-old boy with a right hypochondriac region mass, which was diagnosed as hepatoblastoma on the basis of imaging, raised tumor marker, and biopsy; however, pancreatic origin of the mass was ascertained on exploration and pancreatoblastoma was confirmed on histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Histologically, both show small round cells making the diagnosis challenging on fine needle aspiration cytology and biopsy specimens [1][2][3][4][5][6][7]. Aruna Prabhu et al reported a case of pancreatoblastoma presenting with liver metastases, which was misdiagnosed as HB on small biopsy [8]. This highlights the importance of keeping HB as a differential, in diagnosis and management of liver and pancreatic masses; especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, both show small round cells making the diagnosis challenging on fine needle aspiration cytology and biopsy specimens [1][2][3][4][5][6][7]. Aruna Prabhu et al reported a case of pancreatoblastoma presenting with liver metastases, which was misdiagnosed as HB on small biopsy [8]. This highlights the importance of keeping HB as a differential, in diagnosis and management of liver and pancreatic masses; especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article entitled, “Pancreatoblastoma masquerading as hepatoblastoma: A diagnostic dilemma.”[1] The authors have reported a very challenging clinicoradiologic diagnostic problem. We report a similar case wherein a 7-month-old male infant with abdominal lump, low-grade fever, and slightly elevated serum alpha-fetoprotein (AFP >2000 ng/ml) was initially suspected to be a retroperitoneal germ cell tumor (GCT); however, review of radiology and histopathology revealed the tumor to be a pancreatoblastoma.…”
mentioning
confidence: 99%